SOSIALISASI DAN PEMANFAATAN LIMBAH DAPUR (SAYURAN) UNTUK PEMBUATAN PUPUK ORGANIK CAIR DI DESA NUANEA KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Rolobessy, Mike; Abataman, Ester; Jambormias, Edizon; Siwa, Izak; Leiwakabessy, Christoffol (Universitas Pattimura, 2024)
This research was conducted in contry Nua Nea, Amahai subdistrict, Central Maluku Regency, to over come the problem of lack of fertilizer subsidies and high fertilizer prices. The aim is to provide solutions to farmers through socialization and production of liquid organic fertilizer (POC). The research involves KKN activies that involve students in assisting the community. The material presented includes the benefits of kitchen waste as a source of nutrients and methods for making POC. The research results show that this activity provides new knowledge to the community and incraises awareness of environmental cleanlinees the agricultural potential and environmental cleanliness of Nua Nea state.